Seeking middle ground on social security reform - Koitz, David (Hoover Institution publication, 2001)
This book looks at both the Republican and the Democratic Party plans for Social Security, showing how each confronts significant ideological and political hurdles. David Koitz cuts through the partisan rhetoric that has made social Security one of the most debated programs on the U.S. political scene and looks at both the Republican and the Democratic plans for Social Security, showing important flaws in each.